(untitled) (The Pakistan Development Review, 2012)
This paper considers the impact of the economic rise of China on both firms and competition in middle income countries (locally) and on the world trading system (globally). It examines the size and nature of the shock that China has administered to the world economy, the way in which firms and export sectors in one middle income country have accommodated that rise, some of the frictions and adjustment strains that China’s rise pose for the world trading system, and two cases which I believe to pose threats to the world trading system if the parties involved do not behave with great care. I will argue that integrating China into the global economy in a way that benefits nearly all presents perhaps the most important international trade and trade policy issue of the present era. The shock that the emergence of China is administering to the world economy is larger than any seen previously—and by a large margin. While the huge increase in global production that China has generated brings widespread benefits, there are inevitably stresses and indeed possibly some losers. I start to identify these in two exercises that are reported here, both, for reasons of data availability, carried out on Mexico. One looks at firm adjustment and the other at export margins. I then discuss China’s role in the wider trading system—the WTO and in global imbalances—and finally identify two areas in which the poor handling of the integration of China into the world economy could derail the world trading system. I mention these latter issues not as inevitable disasters but as issues that are sensitive enough to explode if not handled delicately. An important role of economists in policy-making is to discourage inappropriate policies and descent into trade war as a result of the competition that China brings would certainly count as ‘inappropriate’. It is as a warning, no more, that I address them in this paper.